The effect of penetrated oxygen particles on combustion time of coated Al hydride nanoparticles in an oxygenated medium by applying molecular dynamics method via Lennard-Jones and reactive force-field potentials - Habibollahi, Navid; Abdollahi, Ali; Sajadi, S. Mohammad; Toghraie, Davood; Emami, Sobhan; İnç, Mustafa (Elsevier Sci Ltd, 2023)
Today, combustion process (CP) has been used in multifarious industries such as electricity generation, transportation, and heating due to its high energy content. Due to importance of studying CP and good performance of Al-based atomic structures, and since effect of initial temperature in range of 1100 to 1500 K on CP of coated Al hydride nanoparticle (AHNP) has not been investigated, present study investigated CP of ethanol-coated AHNP in an oxygenated and aqueous environment using molecular dynamics (MD) simulation. This simulation done with LAMMPS software. The Verlet algorithm used to determination of physical quantities such as space and velocity. The system temperature adjusted with nose-Hoover thermostat. The potentials of Lennard-Jones (LJ) and reactive force-field (RexFF) used to quantify interactions. It is seen that after 1 ns (equilibration time), temperature of both simulated structures in aqueous and oxygenated environments approach 1000 K. The PE in both simulated atomic samples (in aqueous and oxygenated environments) reaches a certain value after 1 ns, indicating simulated samples' physical equilibrium. By adding ethanol atomic coating, temperature, and PE changes reach numerical values of 1240 K and -558.33 eV, respectively; while the maximum temperature change in an aqueous and oxygenated environment reaches 1191.12 and 1246.89 K.
Keywords: LAMMPS; Nanofluid; Combustion; MD; Oxygen particles